2016
DOI: 10.1259/bjr.20160074
|View full text |Cite
|
Sign up to set email alerts
|

3D turbo field echo with diffusion-sensitized driven-equilibrium preparation technique (DSDE-TFE) versus echo planar imaging in evaluation of diffusivity of retinoblastoma

Abstract: Makoto Obara is an employee of Philips Electronics Japan. He was not involved in data analysis in this study.Objective: Compared with echoplanar (EP) diffusionweighted imaging (DWI), three-dimensional (3D) turbo field echo with diffusion-sensitized driven-equilibrium (DSDE-TFE) preparation DWI obtains images with higher spatial resolution and less susceptibility artefacts. The purpose of this study was to evaluate the feasibility of DSDE-TFE to visualize retinoblastomas compared with EP imaging. Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…On the DSDE-TFE, the mean ADC value was 1.73 ± 0.73 × 10 -3 mm 2 /s. On the EP images, the mean ADC value was 0.93 ± 0.53 × 10 -3 mm 2 /s with significant correlation between DSDE-TFE and EP images [ 12 ]. The variety in mean ADC values in these studies may be because of: 1) different tumour cellularity/stage in different study patient groups; 2) subjective measurement methods; or 3) different technical parameters using different MRI devices for the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the DSDE-TFE, the mean ADC value was 1.73 ± 0.73 × 10 -3 mm 2 /s. On the EP images, the mean ADC value was 0.93 ± 0.53 × 10 -3 mm 2 /s with significant correlation between DSDE-TFE and EP images [ 12 ]. The variety in mean ADC values in these studies may be because of: 1) different tumour cellularity/stage in different study patient groups; 2) subjective measurement methods; or 3) different technical parameters using different MRI devices for the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, echoplanar (EP)-based DWIs yields susceptibility artifacts and image distortion. Hiwatashi A et al [10] correlated EP DWIs and 3D single-shot turbo spin echo to obtain DWIs with higher spatial resolution and less image distortion. They stated that turbo spin-echo sequence is compatible to assess the diffusivity and ADC values of retinoblastoma owing to its insensitivity to field inhomogeneity despite its longer acquisition time.…”
Section: Discussionmentioning
confidence: 99%
“…DWI is based on an echoplanar sequence that is fast yet sensitive to susceptibility artifacts and image distortions, particularly at air-tissue and bone-tissue interfaces. Therefore, DWI of the orbit is challenging [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most individuals, trilateral retinoblastoma is deadly; however, early discovery and aggressive (chemo) therapy may be lifesaving for others. [11,12] Although previous studies have reported the diagnostic accuracy of MRI in detecting intraocular tumour extent and metastasis [13][14][15], our study provides a comprehensive evaluation of the diagnostic accuracy of 3 T ocular MRI, diagnostic role of DWIs, sensitivity, and specificity of different tumour diameter cut off values of post laminar optic nerve invasion (PLONI) and ocular coat invasion as well as the relationship of the abnormal anterior eye segment enhancement in MRI e. This study's goal is to identify intra-orbital lesions by comparing ultrasound and MRI data.…”
Section: Introductionmentioning
confidence: 99%